DEVELOPMENT OF CONTAINER RENTAL STRATEGY FOR BUMN SHIPYARDS SUBCONTRACTORS IN SURABAYA USING QSPM APPROACH - Danis Maulana; Gabriela Surya Erinda; Ovi Prina Gastriani; Mirza Ardiana; Muhammad Lukman Arif (Yayasan Adra Karima Hubbi, 2026)
This study formulates a container rental development strategy for subcontractors operating in state-owned shipyards in Surabaya. A mixed-method design was applied through tenant questionnaires, interviews with internal managers, expert judgement, and document review. The strategic formulation process integrated the IFE, EFE, IE, SWOT, BCG, and QSPM matrices in sequential stages: identifying internal and external factors, determining the business position, generating alternative strategies, comparing business-unit portfolios, and prioritizing the most attractive strategy. The IFE score of 2.84 indicates that the company has a moderate-to-strong internal position, while the EFE score of 2.70 shows a moderate response to external opportunities and threats. The IE Matrix places the company in Cell V, suggesting a Hold and Maintain orientation. SWOT analysis generated market penetration and product development as the most relevant alternatives, while BCG analysis indicated a declining portfolio condition that requires more active market action. The QSPM result shows that market penetration obtained the highest Total Attractiveness Score of 5.07, compared with 4.72 for product development. Therefore, market penetration is recommended through digital promotion, responsive customer service, simplified rental procedures, and customer expansion.